Women as Bioethical Points of Articulation: Maude Jacobs and Public Remembrance of the Cincinnati Whole-Body Irradiation Study. Issue 4 (8th August 2017) - Lynch, John
ABSTRACT: In 1993, the federal government announced it had funded experiments with radiation on Americans. One of those experiments was conducted in Cincinnati by Eugene Saenger, who exposed cancer patients to radiation that many believe hastened their deaths. Maude Jacobs was one of those patients—a single mother with metastatic breast cancer who died 25 days after radiation exposure. She became a key figure in debates about the research and later attempts to remember the research. The use of Jacobs in public memory highlights how depictions of powerless women vivify bioethical public memory. The degree to which these women are silenced facilitates the use of problematic gender stereotypes to craft public memory.